Copper Ion Doped Mullite Composite in Poly (vinylidene Fluoride) Matrix: Effect on Microstructure, Phase Behavior and Electrical Properties - Halder, Kumaresh; Paul, Biplab Kumar; Bagchi, Biswajoy; Bhattacharya, Alakananda; Das, Sukhen (Journal of Research Updates in Polymer Science, 2014)
Highly crystallized copper ion doped mullite composites have been synthesized at 1100°C and 1400°C via sol-gel technique with five different strengths of copper ion and was incorporated in poly-vinylidene fluoride (PVDF) to make doped mullite composite/polymer films. We have studied the effects of this dopant on microstructure, phase transformation, and electrical properties of the polymer films over a wide range of frequency from 1.0 KHz to 2.0 MHz. Characterizations were done by various analytical tools at room temperature. Prominent mullite phases were observed from XRD, FTIR spectroscopy and FESEM characterization of composite polymer. The concentration of the dopant and the sintering temperature were found to be the two basic factors which affect the phase transition of the polymer. The composite film showed maximum dielectric constant of 19.96 at 1 KHz for 1.2M concentration of copper ion doped mullite sintered at 1400°C, compared to 3.09 for the pure polymer. Furthermore, both dielectric constant and electrical conductivity of the composite were found to be highly frequency and temperature dependent. After doping, the A.C. conductivity of the composite was found to increase with increasing temperature following Jonscher’s power law and the electrical resistivity reduced too. Moreover, the results revealed that the phase behaviors and micro structural changes of the copper ion doped mullite composite/polymer film affected its electrical properties with possible impact on its applications.